UPAYA MENINGKATKAN LOYALITAS PELANGGAN MELALUI PEMASARAN RELASIONAL DENGAN DIMEDIASI OLEH KEPUASAN PELANGGAN (STUDI KASUS PADA CV BERKAH MANDIRI SURAKARTA JAWA TENGAH - SRIWIJIASTUTI SRIWIJIASTUTI (JURNAL WIDYA GANECWARA, 2016)
The purpose of this research were: (1) To analyze and measure the influence of relationship marketing to customer loyality (2) To analyze and measure the influence of relationship marketing to customer satisfaction (3) To test the effect of customer satisfaction mediation on the influence of relationship marketing with customer loyality. This research was conducted at CV Berkah Mandiri in Surakarta city. Population used in this research is all customer CV. Berkah Mandiri Surakarta with 179 retailers. Then taken to be a sample of 66 retailers with purposive sampling. Analyzer uses path analysis. Results of data analysis found that there is a perfect mediation effect of customer satisfaction on customer loyalty in CV. Berkah Mandiri Surakarta. This means that relational marketing does not directly increase customer loyalty, but by increasing customer satisfaction, then customer satisfaction can increase customer loyalty. Keywords: relational marketing, customer satisfaction, customer loyalty, path analysis